Surface runoff and nutrient dynamics in cover crop–soybean systems in the Upper Midwest. Issue 1 (20th December 2020) - Weyers, Sharon L.; Gesch, Russ W.; Forcella, Frank; Eberle, Carrie A.; Thom, Matthew D.; Matthees, Heather L.; Ott, Matthew; Feyereisen, Gary W.; Strock, Jeffrey S.
Abstract: Relay‐cropping of the novel oilseeds winter camelina ( Camelina sativa L.) and pennycress ( Thlaspi arvense L.) with short‐season crops such as soybean [ Glycine max (L.) Merr.] can provide economic and environmental incentives for adopting winter cover crop practices in the U.S. Upper Midwest. However, their ability to reduce nutrient loss in surface runoff is unknown. Accordingly, surface runoff and quality were evaluated during three seasonal phases (cover, intercrop, and soybean) over 2 yr in four cover crop–soybean treatments (pennycress, winter camelina, forage radish [ Raphanus sativus L.], and winter rye [ Secale cereale L.]) compared with no‐till and chisel‐till fallow treatments. Runoff was collected with Gerlach troughs and assessed for concentrations and loads of NO3 − –N, total mineral N, soluble reactive P (SRP), and total suspended solids (TSS). Cumulative runoff and nutrient loads were greater during the winter cover phase because of increased snow melt and freeze–thaw released nutrients from living vegetation. In contrast, cumulative TSS was greater during intercrop and soybean phases due to high‐intensity rainfall events with an open soybean canopy. Average TSS loads during the intercrop phase were reduced by 75% in pennycress compared with fallow and radish treatments. During the soybean phase, average TSS, total mineral N, and SRP loads were generally elevated in cover crop treatments compared with no‐till. Overwintering cover crops may contribute to mobility of nutrients solubilized from living or decomposing vegetation; however, this was balanced by their potential to reduce runoff and TSS during high‐intensity spring rains. Core Ideas: Novel easily established winter‐surviving covers are needed in the Upper Midwest. Nutrients from living winter cover vegetation are mobilized in snowmelt runoff. Winter oilseeds reduced runoff and sediments during high‐intensity rain events. Environmental and economic incentives enhance adoption of these novel covers.